Estimating CoM dynamics using a single inertial measurement unit - Gløersen, Ø.; Myklebust, H.; Dysthe, D. K.; Hallén, J. (Sciene and nordic skiing III, 2016)
The center of mass (CoM) trajectory of an athlete is perhaps the single most important parameter in technique analysis. With this information we can make inferences about fluctuations between different forms of mechanical energy (Zoppirolli et al. 2015; Pellegrini et al. 2014), and about the sum of forces applied by the athlete on the environment. However, since the location of the CoM is highly dependent on an athlete`s posture, accurately determining the trajectory during complex movement patterns like cross country skiing is not trivial. Therefore, such measurements have usually been restricted to a laboratory environment using either a force plate or 3D motion capture (MoCap) equipment. The natural environment for cross country skiing includes a long trail and a snowy surface which both are not typically found inside a laboratory. This makes it challenging to study skiing technique quantitatively in its natural environment. A measurement system capable of capturing such data is therefore desirable. Our requirement to such a system is therefore that it should have an unlimited capture volume, and it should not interfere the natural movement pattern. Inertial measurement units (IMUs) are sensors that meet these demands. Such sensors have already been used in multiple studies of cross country skiing technique: Several studies were aimed at automatic classification of sub-technique (StOggl et al. 2014; Marsland et al. 2012; Sakurai et al. 2014; Fasel et al. 2015). Myklebust et al. (2014) were the first to investigate differences between athletes within the same sub-technique. Their results showed that a single IMU positioned at the skier`s os sacrum could discriminate the movement patterns of individual skiers. However, to make inferences about forces and mechanical energy, the relationship between sacrum- and CoM movements needed to be addressed and a study investigating this relationship during ski skating has recently been performed (Myklebust et al. 2015). Results from this study showed a good agreement between CoM and sacrum displacement in the mediolateral direction and somewhat less agreement in the vertical direction. However, in the anteroposterior direction, there were substantial deviations in both the amplitude and timing of the trajectories. The aim of the current study was to investigate the possibility of improving CoM estimation during ski skating using the same experimental setup as Myklebust et al. (2015). We did this by utilizing measurements of the sacrum`s (and thus pelvis`) orientation, in addition to the displacement.